The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/esp.4504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estuarine mudflat formation on tidal prism and large‐scale morphology in experiments

Abstract: Human interference in estuaries has led to increasing problems of mud, such as hyper‐turbidity with adverse ecological effects and siltation of navigation channels and harbours. To deal with this mud sustainably, it is important to understand its long‐term effects on the morphology and dynamics of estuaries. The aim of this study is to understand how mud affects the morphological evolution of estuaries. We focus on the effects of fluvial mud supply on the spatial distribution of mudflats and on how this influe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 59 publications
4
56
0
Order By: Relevance
“…Pilot experiments showed that tilting with a simple sine function results in net exporting systems (supporting information in Braat et al, 2018), which means that the system could be classified as a delta sensu Dalrymple et al (1992). However, we here refer to the system as an estuary, because the relative contribution of river discharge to the tidal volume is too low (≈1%) while ebb and flood currents are much larger and approximately equal (Kleinhans, van der Vegt, et al, 2017).…”
Section: Experimental Setup and Proceduresmentioning
confidence: 75%
See 2 more Smart Citations
“…Pilot experiments showed that tilting with a simple sine function results in net exporting systems (supporting information in Braat et al, 2018), which means that the system could be classified as a delta sensu Dalrymple et al (1992). However, we here refer to the system as an estuary, because the relative contribution of river discharge to the tidal volume is too low (≈1%) while ebb and flood currents are much larger and approximately equal (Kleinhans, van der Vegt, et al, 2017).…”
Section: Experimental Setup and Proceduresmentioning
confidence: 75%
“…The experiment was run for 15,000 tidal cycles, which corresponds to approximately 20 years of natural tidal cycles assuming a semidiurnal tide. The experimental settings were selected based on a set of approximately 30 pilot experiments in which boundary conditions have been varied systematically, which are reported in the supporting information of Braat et al (2018). The settings were selected to ensure that sediment was well above the threshold for motion and that the tidal excursion length, which is the distance a water particle travels in half a tidal cycle, was shorter than the flume length.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…funnel-shaped tidal channels, tidal mouth bars, etc.) Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018). Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…are typically not well preserved (Dalrymple and Choi, 2007). Physical experiments can help bridge this knowledge gap, allowing one to capture delta evolution at a spatial and temporal resolution otherwise impractical in the field (Malverti et al, 2008;Paola et al, 2009;Kleinhans et al, 2012Kleinhans et al, , 2014aStefanon et al, 2012;Braat et al, 2018;Lentsch et al, 2018;Leuven et al, 2018). Recent studies demonstrated that physical experiments are capable of reproducing several typical tidal features, such as ebb deltas (Kleinhans et al, 2012), tidal channel networks (Stefanon et al, 2010;Vlaswinkel and Cantelli, 2011) and tidal estuaries (Kleinhans et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%